Human Resource Service Delivery: Achieving Operational Excellence and Cost Efficiency through Human Resources Shared Services - Loh, Rice Li Na (2009)
Shared service is not a new concept. Many leading companies began to adopt shared services in many functions such as Finance, Human Resources (HR), Technology and many more which has proven its success by achieving cost reduction and operational efficiency. In this paper, I introduce how shared service evolves overtime, and how this is linked to a higher level of the overall service delivery model from a Human Resource perspective. I also discuss the advantages and disadvantages of this undertaking, ways to implement a shared service center and what are the challenges faced by many companies. I have also included business cases whereby companies have shared their first hand experience in implementing shared services, or who have redesigned their service delivery model over last couple of years. The overall paper provides an insight of the trends and importance of HR shared services and how companies can leverage this concept to reap real value from HR professional, through aligning people strategy with business goals.